Dynamic Interaction of Enterovirus 71 and Dendritic Cells in Infected Neonatal Rhesus Macaques - Zhao, Ting; Zhang, Zhixiao; Zhang, Ying; Feng, Min; Fan, Shengtao; Wang, Lichun; Liu, Longding; Wang, Xi; Wang, Qinglin; Zhang, Xiaolong; Wang, Jingjing; Liao, Yun; et al. (Frontiers in Cellular and Infection Microbiology, 2017)
Enterovirus 71 (EV71) is one of the main pathogens responsible for hand, foot and mouth disease (HFMD). Infection with EV71 can lead to severe clinical disease via extensive infections of either the respiratory or alimentary tracts in children. Based on the previous pathological study of EV71 infections in neonatal rhesus macaques, our work using this animal model and an EV71 chimera that expresses enhanced green fluorescent protein (EGFP-EV71) primarily explored where EV71 localizes and proliferates, and the subsequent initiation of the pathological process. The chimeric EGFP-EV71 we constructed was similar to the wild-type EV71 (WT-EV71) virus in its biological characteristics. Similar clinical manifestations and histo-pathologic features were equally displayed in neonatal rhesus macaques infected with either WT-EV71 or EGFP-EV71 via the respiratory route. Fluorescent signal tracing in tissues from the animals infected with EGFP-EV71 showed that EV71 proliferated primarily in the respiratory tract epithelium and the associated lymphoid tissues. Immunofluorescence and flow cytometry analyses revealed that EV71 was able to enter a pre-conventional dendritic cell (DC) population at the infection sites. The viremia identified in the macaques infected by WT-EV71 or EGFP-EV71 was present even in the artificial presence of a specific antibody against the virus. Our results suggest that EV71 primarily proliferates in the respiratory tract epithelium followed by subsequent entry into a pre-cDC population of DCs. These cells are then hijacked by the virus and they can potentially transmit the virus from local sites to other organs through the blood circulation during the infection process. Our results suggest that the EV71 infection process in this DC population does not interfere with the induction of an independent immune response against the EV71 infection in the neonatal macaques.